2015 IEEE 82nd Vehicular Technology Conference (VTC2015-Fall) 2015
DOI: 10.1109/vtcfall.2015.7391170
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of QoS in LTE/EPC Mobile Networks Evaluation of Processing Load

Abstract: International audienceLTE/EPC is an all-IP mobile system which provides higher data rates and lower latency. Nevertheless guaranteeing the QoS is a real challenge since the LTE/EPC QoS model inherits many characteristics of circuit oriented legacy standards. Contrary to usual QoS models of the fixed internet (IP networks), additional signalling procedures are required in order to establish a dedicated bearer for each desired QoS level. This paper introduces an analytical model to evaluate the impact of such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…The normalized Context Loads increase with τ , as the number of average active contexts. On the contrary, in [8] we showed that the Processing Load decreases exponentially with τ reflecting the decreasing number of transitions from CONNECTED to IDLE states. The total Processing Load an Memory Access Rate are obviously increased compared to the BE scenario due to QoS deployment.…”
Section: Table Iv: Scenariosmentioning
confidence: 63%
See 2 more Smart Citations
“…The normalized Context Loads increase with τ , as the number of average active contexts. On the contrary, in [8] we showed that the Processing Load decreases exponentially with τ reflecting the decreasing number of transitions from CONNECTED to IDLE states. The total Processing Load an Memory Access Rate are obviously increased compared to the BE scenario due to QoS deployment.…”
Section: Table Iv: Scenariosmentioning
confidence: 63%
“…In order to evaluate the Processing Load (S), we extend the analysis proposed in [8] by adding procedures related to mobility. This analysis is based on some elements described in [2], which have been enriched introducing our state machine model described above.…”
Section: B Processing Load and Memory Access Rate Evaluationmentioning
confidence: 99%
See 1 more Smart Citation